ANALYSIS OF THE EXTENT OF THE EFFECTS OF COLLECTIVE RES JUDICATA IN RE N. 1.101.937 IN THE LIGHT OF THE CONSTITUTIONALIZATION OF THE PROCESS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The article aims to analyze the controversies that gravitate around the analysis of the constitutionality of article 16 of Law No. 7,347/1985 in the light of the constitutionalization of the process. The scientific reflection involved a deductive and dialectical study of a bibliographic review in order to delimit the arguments around the unconstitutionality of the territorial limitation of the effects of the collective res judicata to the prolator organ of the sentence, elucidating the normative, doctrinal and jurisprudential arguments for this. In addition, the study contemplated the reflection on the principles and constitutional foundations related to the civil process, as well as the understanding of the strengthening of the Democratic State of Law by collective res judicata. Finally, the analysis included considerations about the collective procedural microsystem, structured from a tangle of infraconstitutional normative diplomas, notably, the public civil action (Law n. 7.347/1985), the popular action (Law n. 4.717/1985) and the Consumer Defense Code. The conclusion reached the correct declaration of unconstitutionality, in the midst of the Extraordinary Appeal (RE) n. 1.101.937, of article 16 of Law n. 7.347/1985, because the reasoning of the judgment is consistent with access to justice, isonomy, reasonableness and democratic principle.